(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
The Role of Capital Assistance for Women Farmers, Members of Joint Business Group Ctenggiri Wahanaon Farmer’s Household Income (Case study in Ketewel Village, Sukawati District, Region of Gianyar). Fish processing is an activity carried out by women farmers to help the family economy. Improving the economy of women farmers, KUB Tenggiri Wahana contributes and plays a role in providing capital to support the economic development of women farmers in their area. This aims to increase the household income of women farmers, members of KUB Tenggiri Wahana and their families. Reviewing and analyzing the data in this study, quantitative descriptive analysis methods were used. Based on the studies and analyzes that have been carried out, it is concluded that the household income structure of the woman farmer members of KUB Tenggiri Wahana is about to farm income of Rp 14,389,410 a year (18,35%), the average non-farm income of Rp 41,200,000 a year (52,54%), income from fish processing is about to Rp 22,831,831 a year (29,11%) of the total income of the farmer’s household. The role of capital assistance in fish processing in the form of income contribution of pindang fish is about to Rp 22,831,831 a year (29,11%) of the total income of farmers’ households a year. In this study, it is recommended that the use of capital assistance and fish processing techniques can be monitored then the quantity and quality of pindang fish increases.